2017
DOI: 10.3390/ma10010076
|View full text |Cite
|
Sign up to set email alerts
|

On the Selective Laser Melting (SLM) of the AlSi10Mg Alloy: Process, Microstructure, and Mechanical Properties

Abstract: The aim of this review is to analyze and to summarize the state of the art of the processing of aluminum alloys, and in particular of the AlSi10Mg alloy, obtained by means of the Additive Manufacturing (AM) technique known as Selective Laser Melting (SLM). This process is gaining interest worldwide, thanks to the possibility of obtaining a freeform fabrication coupled with high mechanical properties related to a very fine microstructure. However, SLM is very complex, from a physical point of view, due to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
197
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 383 publications
(213 citation statements)
references
References 87 publications
(185 reference statements)
13
197
0
3
Order By: Relevance
“…Furthermore, it is the first study where the Ti-6Al-4V alloy was strengthened by an oxygen addition during the AM process. The anisotropy of the mechanical properties of SLM and EBM fabricated parts was investigated for metals such as: nickel-based superalloys [9,10], stainless steel [11,12], silumins [13,14] and titanium alloys [15,16]. In contrast to other work, our study is one of the first reported studies showing the anisotropy of the mechanical properties of Ti-6Al-4V investigated on microsamples cut within the SLM and EBM fabricated material.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, it is the first study where the Ti-6Al-4V alloy was strengthened by an oxygen addition during the AM process. The anisotropy of the mechanical properties of SLM and EBM fabricated parts was investigated for metals such as: nickel-based superalloys [9,10], stainless steel [11,12], silumins [13,14] and titanium alloys [15,16]. In contrast to other work, our study is one of the first reported studies showing the anisotropy of the mechanical properties of Ti-6Al-4V investigated on microsamples cut within the SLM and EBM fabricated material.…”
Section: Introductionmentioning
confidence: 95%
“…[234] AlSi alloys show an inhomogeneous composition and grain size across each individual scan track and layer, leading to a heterogeneous distribution of Si-particles during the HT. [24,95,151,240,241] www.advancedsciencenews.com www.aem-journal.com hardening stages, thus removing most of the location dependencies. [235] Yet, a post HT still increases the ductility of AlSi alloys and was found as a suitable option for an adjustment of their mechanical properties.…”
Section: Tensile Strengthmentioning
confidence: 99%
“…[240,241] www.advancedsciencenews.com www.aem-journal.com of the studies to date is provided in Table 29, whereby all studies focus on the mode 1 crack opening case. An overview Dedicated publications to this topic can be found here.…”
Section: Fracture Toughnessmentioning
confidence: 99%
“…The tensile properties of SLM parts fabricated in different building directions depend on the metallurgical bonding between two neighbor melt tracks or layers. When an SLM structure is being built, "layer-layer" and "track-track" molten pool boundaries (MPBs) are generated by multi-layer and multi-track melt pool overlapping, respectively (Figure 2) [16,18]. When the structure is built vertically (90 • ) or horizontally (0 • ), the loading direction caused by an occlusal force would act on the track-track MPB surface or on the layer-layer MPB surface, respectively.…”
mentioning
confidence: 99%
“…When the structure is built vertically (90 • ) or horizontally (0 • ), the loading direction caused by an occlusal force would act on the track-track MPB surface or on the layer-layer MPB surface, respectively. When the part is built diagonally (45 • ), the oriented MPBs are discontinuous not only on the x-y plane but also along the z axis, producing complex loads acting simultaneously along both the layer-layer and track-track MPB surfaces [15,18]. Thus, the differences in MPB formation can eventually influence the mechanical properties of the processed SLM structure.…”
mentioning
confidence: 99%